Women's Empowerment Through the Creation of Totebag Ecoprint at PKK Kereng Bangkirai Mothers - Dwi Nor Safitrianti; Mili Dewanti; Manya Anggela; Okta; Saputra Adiwijaya (Bratasena: Jurnal Pengabdian Kepada Masyarakat, 2026)
Background: The women's empowerment program through the creation of ecoprint totebags is carried out to improve skills and utilization of local natural potential in Kereng Bangkirai Village. Contribution: The results of the questionnaire showed a significant increase in the aspects of knowledge, skills, and sustainability impact, as well as a growing motivation of participants to continue the practice of ecoprinting independently. Method: The training is carried out by applying a participatory method (learning by doing) which includes providing materials, demonstrations, hands-on practice, mentoring, and evaluation. A total of 19 PKK women participated in this activity and succeeded in producing ecoprint totebags using leaves and flowers from the surrounding environment. Results: This program is able to support the development of women's creative economy potential based on the environment